2017
DOI: 10.31055/1851.2372.v52.n1.16908
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización morfo-anatomía y aceites esenciales de Tagetes terniflora y Tagetes minuta (Asteraceae) de Tucumán (Argentina).

Abstract: Summary:The essential oil composition and morpho-anatomy of Tagetes minuta, collected at "El Mollar" and two different populations of Tagetes terniflora collected in Tafí del Valle (Tucumán, Argentina) were studied. The essential oil of aerial parts (flowers and leaves) from both species was analyzed by gas chromatography-mass spectrometry. Qualitative and quantitative differences were observed in the composition of the essential oil from both species. Oxygenated monoterpenes were the dominant compounds in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
(25 reference statements)
0
4
1
8
Order By: Relevance
“…Data on anatomy of the vegetative organ and palynology of reproductive organ in Asteraceae plants have been issued. Regardless of a wide P L A T E 3 Micrograph of petiole anatomy (5a = Cyanthillium cinereum, 6a = Helianthus annus), Field pics (5b = C. cinereum, 6b = H. annus) Lizarraga et al (2017) observed the secretory glandular trichomes on the leaf edges and on stems and petioles of T. minuta which is dissimilar to our findings where the absence of trichomes in petiole was observed. Uniseriate epidermis of T. officinale with cuticle has been observed just like the observation of Gier and Burress (1942) where he reported the epidermis of the stem is a single layer, cutinized wall but parenchymatous layers are 4 in number which is dissimilar to our studies (two layers).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Data on anatomy of the vegetative organ and palynology of reproductive organ in Asteraceae plants have been issued. Regardless of a wide P L A T E 3 Micrograph of petiole anatomy (5a = Cyanthillium cinereum, 6a = Helianthus annus), Field pics (5b = C. cinereum, 6b = H. annus) Lizarraga et al (2017) observed the secretory glandular trichomes on the leaf edges and on stems and petioles of T. minuta which is dissimilar to our findings where the absence of trichomes in petiole was observed. Uniseriate epidermis of T. officinale with cuticle has been observed just like the observation of Gier and Burress (1942) where he reported the epidermis of the stem is a single layer, cutinized wall but parenchymatous layers are 4 in number which is dissimilar to our studies (two layers).…”
Section: Discussioncontrasting
confidence: 99%
“…Lizarraga et al (2017) observed the secretory glandular trichomes on the leaf edges and on stems and petioles of T . minuta which is dissimilar to our findings where the absence of trichomes in petiole was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This genus includes annual or perennial, erect and aromatic herbs with striated stems and pinnate leaves, and some shrubs; it is of great economic importance and includes species of edible and ornamental plants. Extracts of these species are characterized by their insecticidal and nematicidal (chemical pesticide) activity, in addition to their various pharmaceutical applications (Faizi et al, 2011;Lizarraga et al, 2017). The uses, biological activities as the major constituents present in their species are well documented (Tereschuk et al, 2003;Gupta and Vasuveda, 2012;Burlec et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hickey (1974) y Hickey & Wolfe (1975) señalan que los caracteres de la arquitectura foliar ayudan a esclarecer la taxonomía de las angiospermas. Al respecto existen diversos trabajos en angiospermas (Martínez 1984, Martínez-Millán & Cevallos-Ferriz 2005, Rodríguez-Rivera & Romero-Rangel 2007, Cervantes et al 2009; para México, en Asteraceae son escasos (Rojas-Leal et al 2014) y para Tagetes se resume en la inclusión de algunas especies en estudios comparativos sobre morfología y anatomía de la hoja (García-Sánchez et al 2012, Martínez et al 2013, Lizarraga et al 2017, Rivera et al 2019.…”
unclassified
“…En Asteraceae, la anatomía foliar también ha contribuido a delimitar diferentes taxones (Lapp et al 2004, Milan et al 2006, Adedeji & Jewoola 2008, Bombo et al 2012, Lapp et al 2013, Rivera et al 2017. En el caso particular de Tagetes se citan solo algunos estudios de anatomía de raíz, tallo y hojas para caracterizar sus especies con fines taxonómicos (Visintin & Bernadello 2005, García-Sánchez et al 2012, Martínez et al 2013, Lizarraga et al 2017, Schiavinato & Bartoli 2018.…”
unclassified